Magnetic Materials, Thin Films and Nanostructures (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This volume presents eleven original and experimental research studies and review works on current challenges and trends in magnetic materials, thin films, and nanostructures, with a special focus on the design, synthesis, and characterization of various types of magnetic materials, and the study of their structure–property relationships. The developments in new experimental concepts and their state-of-the-art results, which can lead to the transfer, chemical transformation, and high-resolution patterning of advanced thin films and nanomaterials and to the design and fabrication of devices, are also presented and discussed.